Underactuated Rehabilitation Robotics for Hand Function - Zhu, Xuanren; He, Bin (Journal of Robotics and Control (JRC), 2021)
Normal hand function plays an important role in daily life. At present, the incidence of hand dysfunction caused by diseases such as cerebral palsy or stroke is increasing year by year. For the rehabilitation of hand dysfunction, in addition to surgical treatment, effective rehabilitation exercise is also particularly important. It is also a necessary link in the efficient and intelligent development of rehabilitation medicine to develop robots that can effectively help patients with rehabilitation hand functions.In this paper, based on the analysis of the design principles and objectives of the rehabilitation robot with hand function, the kinematics model of the rehabilitation robot with hand function is constructed,based on top-down principle in the design of the machine, the design of the machine hand function rehabilitation robots design optimization process framework, and based on the kinematics model and the virtual prototype technology, build its skeleton model, and carries on the kinematics simulation analysis, the design is verified the correctness of the hand function rehabilitation robot kinematics model.